Reputation-Based Clustering Algorithms in Mobile Ad Hoc Networks - Bidaki, Moazam; Masdari, Mohammad (International Journal of Advanced Science and Technology, 2013)
Clustering is one of the main techniques that are used to increase the scalability of MANETs, but without any security considerations clustering is prone to various security attacks. Some cryptographic-based schemes have been proposed to secure the clustering process, but they are unable to handle the internal attacks. Trust-based clustering schemes have combined the trust management systems with the existing state of art clustering solutions and using cryptographic mechanism these schemes present the most complex and secure clustering solutions that are resilient against both internal and external attackers. In this paper, we present an in-depth analysis of trust-based clustering schemes and illustrate how reputations are integrated in these schemes. Then we compare them based on the various trust metrics and finally conclude with open research issues.